(untitled) (The Batuk, 2021)
This article analyzes and evaluates Henrik Ibsen’s most controversial drama “Ghosts” from naturalistic point of view. Naturalism views human life in relation to internal and external environment. It insists on the effect of the past that shapes the present life of human beings. Based on this philosophy of life, this article examines how the life of the leading characters Mrs. Alving and her son Oswald has been influenced. Mrs. Alving’s present values and views on life have a concern with conventional and religious past whereas Oswald’s philosophy of life is guided and governed by his dead father. This article also shows heredity and genetic transformation are biological facts that affect human life. Thus, the object of this article is to explore how human beings are controlled by the inescapable past.